The Expense of the General Budget Tables Using Excel Macro Program - Intidhar Kheder Mohammed Ali (Journal of Madenat Alelem University College, 2020)
The research aims to prepare the General Budget Tables using the advanced tables application - Excel by designing a program which includes the Macro- automatic execution formulas. The inputs can be entered the specified mathematical equations and pre-prepared software formats to obtain the required data works with precision and high speed despite of the dense input data which reduces a lot of time and effort.